PERANAN ISTRI NELAYAN DALAM MEMBANTU MENINGKATKAN PENDAPATAN KELUARGA DI KELURAHAN SAMBOJA KUALA KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Devi Yuliana Wahyuni; Gusti Haqiqiansyah; Eko Sugiharto (2339-1324, 2015)
The research aims to know the role of fishermen’s wife to develop the family income and to assess her contribution to the living of the family. There were 20 fishermen’s wives as the sample of this research. The sampling method was used the purpose sampling. Primary data were gathered by interview and secondary data were collected from sources such as books, journals and research reports. Research analyses were started by studying all the resources then they were analyzed by three angulation and followed by tabulation analysis. Based on data it can be concluded that two roles of wife were she is acting as the house wife and generating family’s income. Furthermore, as the fishermen’s income was not enough for living and then the total family one was also influenced by wife contribution. This was calculated to more than 28% of the total family income.